2011
DOI: 10.4314/njpar.v31i2.69472
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between HIV/AIDS and poverty:Acase study of two cities in Abia State, Nigeria

Abstract: A study was conducted between March and September 2007 to determine the relationship between HIV/AIDS and poverty in two urban cities in Abia State, Nigeria. A total of 382 respondents, made up of 235 (61.5%) HIV/AIDS positive patients, 119 (31.2%) HIV-negatives, while 28 (7.3%) were of unknown status. Using educational level, employment status and salary structure, it was found that the disease in the state was not caused by poverty. It was therefore concluded that drastic measures besides poverty alleviation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 3 publications
1
3
0
Order By: Relevance
“…Results obtained also shows a variation in the distribution of infection in relation to sex, age, occupation and level of education as agreed in similar studies [10]. In Figure 1, the prevalence of Elephantiasis Infection on Leg %, [11] reported that men were found to have a higher prevalence of the condition than women which also agrees with [12] that Lymphatic filariasis is an important public health problem in Ogidi as observed elsewhere in Nigeria. This could be attributed to inhabitants being exposed to mosquito bites, not using mosquito net and unhealthy environment.…”
Section: Table 1 and Table 2: Prevalence Of Lymphatic Filariasis Amon...supporting
confidence: 86%
“…Results obtained also shows a variation in the distribution of infection in relation to sex, age, occupation and level of education as agreed in similar studies [10]. In Figure 1, the prevalence of Elephantiasis Infection on Leg %, [11] reported that men were found to have a higher prevalence of the condition than women which also agrees with [12] that Lymphatic filariasis is an important public health problem in Ogidi as observed elsewhere in Nigeria. This could be attributed to inhabitants being exposed to mosquito bites, not using mosquito net and unhealthy environment.…”
Section: Table 1 and Table 2: Prevalence Of Lymphatic Filariasis Amon...supporting
confidence: 86%
“…In some states, urban prevalence figures are higher than that of the rural, though the reverse is the case in others (Obi et al, 2010). Interestingly, the spread of HIV/AIDS is attributed to poverty (Obi et al;2010). Whereas poverty in Nigeria is older than the HIV/AIDS epidemic as the first case of AIDS in Nigeria was only reported in 1986 (NACA, 2014), the sudden rise of the latter has bestowed a bicausal relationship that is mutually reinforcing thereby justifying the focus of many scholars on the study of HIV/AIDS as the major factor in the rise of orphaned children.…”
Section: Orphans and The Challenges Of The Under-privileged In Africamentioning
confidence: 93%
“…There is also a considerable variation in the urban/rural prevalence of HIV/ AIDS among the states in Nigeria. In some states, urban prevalence figures are higher than that of the rural, though the reverse is the case in others (Obi et al, 2010). Interestingly, the spread of HIV/AIDS is attributed to poverty (Obi et al;2010).…”
Section: Orphans and The Challenges Of The Under-privileged In Africamentioning
confidence: 99%
See 1 more Smart Citation